Analisis Konflik dan Resolusinya pada Perpecahan Etnis Porodisa di Kota Salatiga - Bawoel, Silvani Agnes; Esra Kudubun, Elly; Roberth Siahainenia, Royke (Jurnal Interaksi Sosiologi, 2025)
This study analyzes the conflict and resolution processes that occurred in the ethnic division of Porodisa in Salatiga City, leading to the establishment of a new organization called PERSADA. This conflict was triggered by controversies surrounding changes to the organization’s identity, such as the alteration of the name, logo, and Articles of Association (AD/ART) without involving all members. Although Porodisa initially served as a gathering place for students from Talaud, dissatisfaction arising from unilateral decisions led to division. Utilizing a qualitative method based on interviews, observations, and documentation, the analysis is conducted through Johan Galtung's Conflict Triangle Theory, which provides insight into the interactions between attitudes, behaviors, and contradictions and can help formulate more effective conflict resolution strategies. The findings indicate that, despite Porodisa and PERSADA now operating as separate entities, there is a strong desire from both sides to rebuild harmonious relationships. The conflict resolution process is recommended through open dialogue and mediation by neutral third parties, reflecting Galtung's peacemaking approach to create an inclusive and constructive environment. Emphasizing transparent communication and the participation of all members in decision-making, this research underscores that the sustainability and harmony within the organization are significantly dependent on involvement and sensitivity to shared needs. This is expected to strengthen solidarity and ensure the group’s longevity in the future.